2020
DOI: 10.1063/1.5142563
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of sodium and zinc ionomers: Effects of neutralization and valency

Abstract: Using a parallel-plate rheometer equipped with a partitioned plate and the Sentmanat extensional rheometer fixture, a full rheological characterization of several commercial ionomers (sodium and zinc) and their corresponding parent copolymers has been carried out. Particular emphasis has been placed on the distribution of the relaxation times to identify the characteristic times, such as reptation, Rouse, and lifetime of associations that are associated with entanglements, ionic and hydrogen bonding associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The lifetime of these ionic bridges depends on their ionic environment and appears to shorten with increasing monovalent cation (mainly potassium) concentration. Usually, the sticker lifetime is described using an empirical Arrhenius form , where the activation energy is determined from the linear rheology using Van ’t Hoff plots [ 13 , 23 , 26 , 40 , 51 , 52 , 53 ]. In this section, we argue that this activation energy might not be the one that is of importance to the non-linear rheology, because a different mechanism of sticker opening takes over.…”
Section: Experimental and Modelling Methodsmentioning
confidence: 99%
“…The lifetime of these ionic bridges depends on their ionic environment and appears to shorten with increasing monovalent cation (mainly potassium) concentration. Usually, the sticker lifetime is described using an empirical Arrhenius form , where the activation energy is determined from the linear rheology using Van ’t Hoff plots [ 13 , 23 , 26 , 40 , 51 , 52 , 53 ]. In this section, we argue that this activation energy might not be the one that is of importance to the non-linear rheology, because a different mechanism of sticker opening takes over.…”
Section: Experimental and Modelling Methodsmentioning
confidence: 99%
“…To solve Eqs. (20)(21) in the long-time limit, we make the useful approximation that at an intermediate time t = t * the distribution is equilibrated for small stretches λ ≤ λ * , while the large-stretch tail of the distribution is unoccupied. Hence, at t = t * the distribution is given by P 0 (0, y) = c c P eq 0 Θ(−y + y * )…”
Section: B Long-time Limit Of the Two-state Modelmentioning
confidence: 99%
“…We previously found in collaboration with Laity and Holland that the silk protein exhibits intermolecular reversible cross-links [7,22]. While these associations shift the alignment-tostretch transition to smaller strain rates by replacing the usual Rouse relaxation dynamics for 'sticky Rouse' relaxation [12][13][14][15][16][17][18][19][20][21], this is not the full story, for the Bombyx mori silkworm manages also to generate the opposite effect during pupation: when the silkworm starts spinning the material it actually chemically reduces this relaxation time through the addition of potassium cations [7,22]. Intriguingly, the group of Holland discovered that the structural features of the silk fibre is significantly enhanced through a gradient in the pH along the spinning duct, suggesting an exquisitely controlled local rheology [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that microscopic chain stretch and the consequent macroscopic strain hardening is triggered by a small number of calcium bridges [13,15] that act as 'sticky' reversible intermolecular crosslinks akin to those in synthetic 'sticky polymers' [16][17][18][19][20][21][22][23][24]. For this class of molecules, a molecular understanding of the non-linear rheology and crystallization of 'sticky polymers' has so far relied on computationally expensive (coarse-grained) molecular dynamics simulations [5,[25][26][27][28][29]. Simpler molecular models coarse-grained at the level of entanglements, but able to capture the vital slow processes, remain absent.…”
mentioning
confidence: 99%